ASEAN Integration Monitoring Report - ASEAN Secretariat; World Bank (Jakarta: ASEAN Secretariat and the World Bank, 2014)
The Association of Southeast Asian Nations (ASEAN) is a community of more than 600 million people living in ten countries in one of the most dynamic regions of the world. Consistent with this, ASEAN's share of world GDP and world trade has sharply increased over the past decades. In 2003, ASEAN's regional integration agenda was significantly deepened when ASEAN Member States adopted the ambitious goal of forming an ASEAN Economic Community (AEC) by 2015. These goals were crystallized in the highly specific targets set for creating a 'single market and production base' in the ASEAN Economic Community Blueprint of 2007, signed by the Heads of the Governments of the ASEAN countries. The focus of the report is on policy and market integration outcomes achieved in ASEAN Member States (AMS) as part of the Pillar One of the ASEAN Economic Community (AEC) formation process. The aim is to assess progress drawing on evidence from a large range of indicators on policies and outcomes. The report then suggests priorities for future actions for implementing the AEC 2015 goals. This report is based on the inception report presented to and endorsed by the Senior Economic Officials' Meetings of the ASEAN last year and on the presentation on early findings also to the SEOM. The earlier version of this report was also presented to the 45th ASEAN Economic Ministers' Meetings in Bandar Seri Begawan, Brunei Darussalam in August 2013. This report is intended to complement the recent mid-term review report by the Economic Research Institute for ASEAN and East Asia (ERIA, 2012), which has focused more on progress with agreements and commitments for achieving AEC 2015 goals.